Saline versus Lactated Ringer's Solution: The Saline or Lactated Ringer's (SOLAR) Trial. (April 2020) - Maheshwari, Kamal; Turan, Alparslan; Makarova, Natalya; Ma, Chao; Esa, Wael Ali Sakr; Ruetzler, Kurt; Barsoum, Sabri; Kuhel, Alan G.; Ritchey, Michael R.; Higuera-Rueda, Carlos; Kopyeva, Tatyana; Stocchi, Luca; et al.
Abstract : Background: Both saline and lactated Ringer's solutions are commonly given to surgical patients. However, hyperchloremic acidosis consequent to saline administration may provoke complications. The authors therefore tested the primary hypothesis that a composite of in-hospital mortality and major postoperative complications is less common in patients given lactated Ringer's solution than normal saline. Methods: The authors conducted an alternating cohort controlled trial in which adults having colorectal and orthopedic surgery were given either lactated Ringer's solution or normal saline in 2-week blocks between September 2015 and August 2018. The primary outcome was a composite of in-hospital mortality and major postoperative renal, respiratory, infectious, and hemorrhagic complications. The secondary outcome was postoperative acute kidney injury. Results: Among 8, 616 qualifying patients, 4, 187 (49%) were assigned to lactated Ringer's solution, and 4, 429 (51%) were assigned to saline. Each group received a median 1.9 l of fluid. The primary composite of major complications was observed in 5.8% of lactated Ringer's versus 6.1% of normal saline patients, with estimated average relative risk across the components of the composite of 1.16 (95% CI, 0.89 to 1.52; P = 0.261). The secondary outcome, postoperative acute kidney injury, Acute Kidney Injury Network stage I–III versus 0, occurred in 6.6% of lactated Ringer's patients versus 6.2% of normal saline patients, with an estimated relative risk of 1.18 (99.3% CI, 0.99 to 1.41; P = 0.009, significance criterion of 0.007). Absolute differences between the treatment groups for each outcome were less than 0.5%, an amount that is not clinically meaningful. Conclusions: In elective orthopedic and colorectal surgery patients, there was no clinically meaningful difference in postoperative complications with lactated Ringer's or saline volume replacement. Clinicians can reasonably use either solution intraoperatively. Abstract : In a large single-center alternating cohort trial of patients having elective colorectal or orthopedic surgery, there was no clinically meaningful difference in the risk of a composite of in-hospital mortality and major postoperative complications including renal, respiratory, infectious, and hemorrhagic complications.Supplemental Digital Content is available in the text.